Association of LDL-C/HDL-C Ratio With Stroke Outcomes Within 1 Year After Onset: A Hospital-Based Follow-Up Study - Liu, Li; Yin, Ping; Lu, Chong; Li, Jingxin; Zang, Zhaoxia; Liu, Yongdan; Liu, Shuang; Wei, Yafen (Frontiers in Neurology, 2020)
Stroke remains a leading cause of death and disability. The low-density lipoprotein cholesterol to high-density lipoprotein cholesterol (LDL-C/HDL-C ratio) ratio has been confirmed to be a predictor of stroke. However, few studies have assessed the prognostic impact of the LDL-C/HDL-C ratio for stroke patients. We aimed to investigate the relationship between the LDL-C/HDL-C ratio and the prognosis following stroke in Chinese patients. A total of 3,410 patients who had experienced their first ischemic stroke was recruited to this study within 72 h of stroke onset. The patients were followed for at least 12 months. A multivariate regression analysis was used to assess the association between the LDL-C/HDL-C ratio and prognosis following stroke. We considered the LDL-C/HDL-C ratio as a continuous variable and stratified patients according to the LDL-C/HDL-C ratio quartile. A higher LDL-C/HDL-C ratio was associated with lower rates of death, recurrence, and moderate disability (defined as a modified Rankin scale score >2) at 3 months. Using group 1 as the reference group, the relative risk (RRs) at 3 months for death were 0.45 (95% confidence interval [CI]: 0.27, 0.77) for group 2, 0.58 (95% CI: 0.34, 0.98) for group 3, and 0.97 (95% CI: 0.60, 1.56) for group 4; for recurrence, the RRs were 0.75 (95% CI: 0.56, 0.99) for group 2, 0.65 (95% CI: 0.48, 0.89) for group 3, and 0.55 (95% CI: 0.39, 0.78) for group 4; and for moderate disability, the RRs were 0.74 (95% CI: 0.55, 0.99) for group 2, 0.65 (95% CI: 0.47, 0.89) for group 3, and 0.55 (95% CI: 0.39, 0.77) for group 4. At 12 months, patients in group 2 were the most protected against ischemic stroke death (RR: 0.57; 95% CI: 0.34, 0.95). However, there were no associations between the LDL-C/HDL-C ratio and stroke recurrence or moderate disability. A higher LDL-C/HDL-C ratio was found to protect against death, recurrence, and moderate disability at 3 months. However, there was no significant association between the LDL-C/HDL-C ratio and stroke recurrence or moderate disability at 12 months. These results nonetheless suggest that a higher LDL-C/HDL-C ratio was associated with short-term stroke prognosis.